Land productivity and agri-environmental indicators: A case study of Western Balkans - Danilo okić; Bojan Matkovski; Marija Jeremić; Ivan urić (Land, 2022)
Due to the environmental radicalization of European politics, which is reflected in the European Green Deal, Farm to Fork strategy, and new CAP 2023–2027, this paper aims to determine the impact of agri-environmental indicators on soil productivity based on the land productivity function model. The paper focuses on the Western Balkans countries, which are in the process of European integration and which, in the coming period, need to harmonize their agricultural policy with the CAP. First, the aggregate Cobb–Douglas production function has been used to create a land productivity function. Then, the sources of land productivity growth have been calculated, which can be particularly interesting in the context of agri-environmental indicators, such as fertilizer use and livestock density. The research results showed that land productivity is the most elastic concerning changes in the number of livestock units per hectare. Consequently, reducing livestock units had a markedly negative effect on productivity. In addition, the research results showed that using mineral fertilizers is a crucial source of growth in land productivity in these countries. These results imply that the creators of the agricultural policy must carefully assess the pace at which they will harmonize ecological and economic goals, especially if they take into account the current Ukraine crisis that can disrupt the food market.
Keywords: 330; agri-environmental indicators; fertilizer use; European Green Deal; CAP 2023-2027